'What lies behind the filter?' Uncovering the motivations for using augmented reality (AR) face filters on social media and their effect on well-being. (March 2022) - Javornik, Ana; Marder, Ben; Barhorst, Jennifer Brannon; McLean, Graeme; Rogers, Yvonne; Marshall, Paul; Warlop, Luk
Abstract: Augmented reality (AR) filters are a popular social media feature affording users a variety of visual effects. Despite their widespread use, no research to date has examined either 'why' people use them (i.e., motivations) or 'how' their usage makes people feel (i.e., well-being effects). Through the uses and gratifications theory supported by a sequential mixed-method approach (interviews N = 10 and survey N = 536), we provide three overarching contributions. First, based on prior literature and a qualitative study, we identify nine motivations that can potentially drive AR face filter usage on Instagram. Our survey indicates that seven of those motivations (e.g., creative content curation, social interactions) are significant drivers of usage behaviours, while two (true self-presentation and silliness) did not have a significant impact. Second, we provide nuanced insights into the multi-faceted nature of the self-presentation motives underpinning AR face filter use (ideal, true and transformed self-presentation). Lastly, we show filter usage can have both positive and negative well-being effects depending on the underlying motivation. The results offer important implications for policymakers, site designers and social media managers. Highlights: We identify seven motivations that drive the use of AR face filters. These motivations drive either frequency use or exploratory use. Users engage in true, ideal or transformed self-presentation via the filters. AR face filters impact users' well-being, i.e. self-acceptance and positive affect.